Waste materials in construction : putting theory into practice : proceedings of the International Conference on the Environmental and Technical Implications of Construction with Alternative Materials, WASCON'97, Houthem St. Gerlach, the Netherlands, 4-6 June 1997 /: putting theory into practice : proceedings of the International Conference on the Environmental and Technical Implications of Construction with Alternative Materials, WASCON'97, Houthem St. Gerlach, the Netherlands, 4-6 June 1997. (1997) - Unknown
No abstract available